The norming sets of multilinear forms on a certain normed space $\mathbb{R}^n$ - Sung Guen Kim (Математичні Студії, 2024)
Let $n, m\in \mathbb{N}, n, m≥ 2$ and $E$ a Banach space. An element $(x_1, …, x_n)\in E^n$ is called a~norming point of $T\in {\mathcal L}(^n E)$ if $\|x_1\|=…=\|x_n\|=1$ and $|T(x_1, …, x_n)|=\|T\|,$ where ${\mathcal L}(^n E)$ denotes the space of all continuous $n$-linear forms on $E.$ For $T\in {\mathcal L}(^n E),$ we define ${Norm}(T)$ as the set of all $(x_1, …, x_n)\in E^n$ which are the norming points of~$T.$